2021
DOI: 10.3390/f12121757
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast DNA Diversity in Populations of P. sylvestris L. from Middle Siberia and the Romanian Carpathians

Abstract: Scots pine is one of the dominant conifer species in forest ecosystems of the boreal zone in Eurasia. Knowledge of the genetic structure and the level of genetic variability of Scots pine populations is relevant for the development of measures aimed at conservation of species’ diversity. In this study, we used ten paternally inherited chloroplast microsatellite loci to investigate the genetic diversity of nineteen Scots pine populations from Middle Siberia and the Romanian Carpathians. The results of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Decrease of population size, due to fires and logging, diseases and environmental pollution leads to the reduction of genetic diversity (Ellstrand and Elam, 1993). In the study by Sheller et al (2021) the lowest level of chloroplast DNA haplotype diversity was also detected in one of the Balgazyn Scots pine populations, confirming the need the conservation of these genetic resources.…”
Section: A B Figurementioning
confidence: 76%
See 1 more Smart Citation
“…Decrease of population size, due to fires and logging, diseases and environmental pollution leads to the reduction of genetic diversity (Ellstrand and Elam, 1993). In the study by Sheller et al (2021) the lowest level of chloroplast DNA haplotype diversity was also detected in one of the Balgazyn Scots pine populations, confirming the need the conservation of these genetic resources.…”
Section: A B Figurementioning
confidence: 76%
“…The genetic specificity of many population groups in marginal parts of the species' distribution range was also observed in Iberia, Transcaucasia, Asia Minor and Eastern Siberia (Prus-Glowacki and Stephan, 1994;Sinclair et al, 1999;Sannikov et al, 2005;Cheddadi et al, 2006;Naydenov et al, 2007;Pihäjärvi et al, 2008;Dering et al, 2017Dering et al, , 2021Sheller et al, 2023). At the same time, a significant homogeneity of populations was revealed within certain regions of Scandinavia, Central, Western and Eastern Europe, Siberia (Goncharenko et al, 1993;Zhelev et al, 1994;Sinclair et al, 1999;Robledo-Arnuncio et al, 2005;Cheddadi et al, 2006;Pihäjärvi et al, 2008;Semerikov et al, 2018;Sheller et al, 2021Sheller et al, , 2023.…”
Section: A B Figurementioning
confidence: 85%
“…SSRs are widespread throughout plastid genomes across different species and are extensively employed in plant population studies [58][59][60]. In this study, the identified SSRs varied in number, with counts ranging from 198 in C. nitrarium to 208 in C. dzhungaricum plastomes, resulting in a total of 814 SSRs (Table 4).…”
Section: Discussionmentioning
confidence: 87%
“…This is also the case between Scottish and continental populations, and it is only between European and Anatolian populations that cpSSR structure is apparent [ 96 ]. A recent establishment of northwest populations together with homogenising pollen-mediated gene flow likely explain the absence of sub-population differentiation in Europe [ 6 , 93 , 106 , 107 ]. In this study, only Dale Wood was differentiated (Table S 4 , Figure S 2 ), and this was due to very low variation (Fig.…”
Section: Discussionmentioning
confidence: 99%